Penyuluhan Sistem Integrasi Tanaman-Ikan, Pemasaran Hasil Pertanian, dan Motivasi Kerja untuk Meningkatkan Pendapatan Petani di Desa Tambaksari Kidul: Extension of Plant-Fish Integration System, Agricultural Product Marketing, and Work Motivation to Increase Farmer Income in Tambaksari Kidul Village - Nugraha, Fadhil Adi; Utami, Pujiati; Adella, Shinta; Anggara, Bayu; Apriliani, Dwi Wahyu (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Kembaran District in Banyumas Regency is a rapidly developing residential area that maintains agricultural regions, including Tambaksari Kidul Village. This village has high agrarian potential, fertile soil, and a yearly stable water supply. Local farmers are members of the